Boas políticas e práticas tributárias para fortalecer a arrecadação do IPTU dos municípios brasileiros - Oliveira Neto, Mauro de (2024)
This work consists of two studies, each presented in its own chapter. Regarding the first study, utilizing a literature review of scientific articles, the aim was to identify and understand the good tax policies and practices that can contribute to enhancing the fiscal capacity of Brazilian municipalities through the strengthening of the collection of the Urban Property and Land Tax (IPTU). This study was motivated by the national political-financial scenario in which Brazilian municipalities are immersed, characterized by the constitutional assignment of various responsibilities, a high dependence on intergovernmental transfers, a loss of autonomy, and the underutilization of the IPTU for generating own revenues. The study is characterized as applied, qualitative, exploratory, and descriptive, with bibliographic research adopted as the investigative procedure. From the review of the 32 selected articles from one of the largest virtual scientific collections in Brazil, 13 strategies were identified to better seize opportunities and/or address the main contemporary problems in municipal public administration regarding the low utilization of IPTU collection. As for the second study of this work, through a discussion in light of good tax policies and practices to strengthen the collection of IPTU in Brazilian municipalities, the objective was to reveal the challenges faced by the Municipality of Uberlândia/MG, as well as the expected advantages, when adopting scientific methodology in property valuation for the purpose of IPTU collection. This research was conceived in response to the need for updating the Generic Value Plan (PGV) and the prioritization given to the direct comparative method of market data according to NBR 14.653-2 in mass property valuation. The study is characterized as applied, qualitative, descriptive, and a case study investigation strategy based on participant observation. The perceived challenges are related to stored data, property registration, human resources, the software used, market data collection, the frequency of PGV updates, the handling of specific cases, legislative approval, and geoprocessing. The desired advantages pertain to tax justice, increased revenue, and the substantiation of property valuations.